Suitability of Worker Characteristics and Job on Work Environment In the Furniture Industry of West Java, Indonesia - Rizki, Dwiki Fatur; Yewon, Kim; Alfin, Muhammad (Al Makki Publisher, 2024)
This research aims to describe the work environment in the furniture industry based on the suitability of workers and job characteristics. This research uses descriptive qualitative methods and is conducted on cases in the furniture industry in West Java, Indonesia. Data collection techniques are performed using interviews, observation, and documentation and analyzed inductively. The research results show that the work environment in the carved furniture industry can be identified based on the suitability of job characteristics. They are work risks faced by establishing safe work environment boundaries, worker characteristics regarding their role by work procedures and work experience, and the value of the agreement norms that form safe environmental behavior and interactions. Furthermore, the results can be used as recommendation material for further research related to work environment issues that dig deeper into other phenomena based on cultural characteristics, safety behavior, and wage mechanisms so that the utility value of wages and risks received can be known.